STUDY OF BEHAVIOURAL ADAPTATION AGAINST CHANGES TO THE LAYOUT OF THE OFFICE WORKSPACE AT COVID-19 PANDEMIC PERIOD - Suharto, Moh. Fachruddin; Zuldesmi, Zuldesmi; Attaufiq, Muhammad Muhdi; Kawatu, Freike Eugene (JAMBURA Journal of Architecture, 2024)
The Covid-19 pandemic has caused many changes to human lifestyles, one of which is changing the way we work and the way we define the 'workplace' which is known as the office. As a result of this phenomenon, there is an adaptation of user behaviour (office employees) to changes in the layout of the workspaces in their offices. This research provides an overview of the adaptation to changes in the layout of the workspace and changes in employee behaviour in their workplace during the Covid-19 pandemic. The adaptation applied is the Adaptation to New Habits (ANH) as a realization of the implementation of health protocols that have been set by the government. In this study, employees' perceptions will be measured based on physiological factors in the form of sources of information they get to implement the adaptation to new habits and how this encourages them to implement health protocols during the Covid-19 pandemic. The research method used is a qualitative description which is then quantified to determine the tendency of office employees to adapt  to changes in the layout of office workspace. In addition, it also seeks to understand, examine and interpret the meaning of an adaptation event and changes in human behaviour toward changes in workspace layout in the Covid-19 pandemic situation from the perspective of the researchers themselves. The results of this study reveal that in the adaptation process there are changes due to essential needs related to health protocol procedures in the office and space requirements that are adapted to their functions.